Pengembangan Media Pembelajaran Video Animasi Pada Materi Menulis Puisi Kelas X SMA - Siti Malahayati Ritonga; Ali; Deliani (Medan Resource Center, 2022)
This study aims to: (1) Describe the Development Process of Canva Animation Video Learning Media Writing Poetry for Class X SMA, (2) Describe the Validity of Material Experts and Media Experts About Development of Learning Media Canva Animated Video Writing Poetry for Class X SMA, (3) Describe the Feasibility Canva Animation Video Learning Media Products for Class X High School Poetry Writing. Sources of data in this study in the form of a questionnaire. The type of data used is descriptive qualitative data as the main data collected through an instrument with a Likert scale. Respondents in this study were Material Experts and Media Experts. This research method is a deve lopment research using the Borg and Gall Model which was adjusted in 6 stages because it was still in a state of the Covid-19 pandemic, namely (1) needs analysis, (2) Product Specification Planning, (3) Product Design, (4) Product Validation. , (5) Product revision/improvement, (6) Dissemination. The material expert's response, obtained the average overall aspect of the material in the